Compare the Teachers Coaching Behavior of School Administrators Under Secondary Education Service Area Office Nongkhai - Chantharawilai, Thanaboon; Jeekratok, Kanisorn; Homsin, Nawattakorn (Academic MCU Buriram Journal, 2024)
The purposes of this research were: 1) to compare the teachers coaching behavior of school administrators under secondary education service area office Nongkhai categorized by gender, age, educational status, and school size. The sample group used in this study consists of 19 administrators and 178 teachers within a school under the jurisdiction of the Educational Service Area Office of Secondary Education in Nong Khai. The data on government officials, administrators, and teachers in the school are derived from the annual performance report for the fiscal year 2021. In total, there are 197 individuals, comprising 89 males and 108 females. Among them, 66 individuals are aged between 20 and 30, 81 are aged between 31 and 40, and 50 are aged 41 and above. There are 112 individuals without academic rank, 63 with a proficient academic rank, and 22 with a higher than proficient academic rank. The school sizes are distributed as follows: 97 individuals in small schools, 44 in medium-sized schools, and 56 in large special schools. The research instrument were a questionnaire on the current situation and a questionnaire on the teachers coaching behavior of school administrators. The statistics for data are analyzed by average and standard deviation and comparing the teachers coaching behavior of school administrators was conducted using the F-test Independent and t-test in research terminology. The research result found that: The results of the comparison on the teachers coaching behavior of school administrators under secondary education service area office Nongkhai are as follows: 1) The results of the comparison of the teachers coaching behavior of school administrators under secondary education service area office Nongkhai categorized by gender show no significant differences across all five dimensions. 2) The results of the comparison of the teachers coaching behavior of school administrators under secondary education service area office Nongkhai categorized by age show no significant differences across all five dimensions. 3) The results of the comparison of the teachers coaching behavior of school administrators under secondary education service area office Nongkhai categorized by academic credentials show no significant differences across all five dimensions. 4) The results of the comparison of the teachers coaching behavior of school administrators under secondary education service area office Nongkhai categorized by size of school show no significant differences across all five dimensions.